Superiority of the Native Seen in the Tone of The Track to Bralgu by Bozic Wongar - Dearty Crima; G. Fajar Sasmita Aji (Universitas Sanata Dharma, 2014)
This paper focuses on The Track to Bralgu, a twelve-chapter novel written by Bozic Wongar. The novel is concerned with the destruction and exploitation of the land and the Aborigines. The novel emphasizes the superiority of the colonizer as a surface representation, and the superiority of the colonized as the representation of depth. The aim of this study is to obtain an understanding of how the tone of The Track to Bralgu leads readers to the superiority of the colonized. The objectives are first, to explain the steps of examining the tone of The Track to Bralgu and to explain how its tone can lead readers to the superiority of the colonized; second, to analyze the superiority of the colonizer as a surface representation of The Track to Bralgu; and third, to examine the tone of The Track to Bralgu which brings the idea of the superiority of the colonized. The method that was conducted in the study was the library research, for all the reference textbooks applied in the study were gained from the library. In conducting the analysis, a postcolonial approach was applied. By applying a postcolonial approach, the researcher is able to understand the broad outline of the relation between the colonizer and the colonized presented in the novel. The result of the study shows in The Track to Bralgu, the superiority of the colonizer is depicted through the superiority of tools and technology, while the superiority of the colonized is depicted in its close relation to nature. The tone of The Track to Bralgu is cynical and it brings the idea of the superiority of the colonized because its tone is examined from the colonizeds cynical view of the colonizer. Keywords: superiority, tone, colonized, colonizer, postcolonial